Adequately Iodized Salt Utilization and Associated Factors among Households in Tach Armachio District, Northwest Ethiopia: A Community-Based Cross-Sectional Study - Worku Mamo; Terefe Derso; Solomon Gedlu Nigatu (Journal of Nutrition and Metabolism)
Background. For the synthesis of thyroid hormones, iodine is a crucial trace element. Iodine deficiency disorders affect all groups particularly: pregnant, young women and children. Iodine deficiency disorder has been recognized as a serious public health issue in Ethiopia. Therefore, this study planned to assess iodized salt utilization and associated factors at the household level. Methods. A community-based cross-sectional study was conducted from January 25 to February 24, 2019, in Tach Armachio district, Northwest Ethiopia. A single population proportion formula was used to calculate the sample size and a total of 555 households were sampled. A multistage sampling technique was conducted to select the household. An iodometric titration method was performed. A structured, pretested, and face-to-face interview questionnaire was used to collect data; then, it was entered in Epi Info 7 and exported to SPSS version 25 for analysis. Bivariable and multivariable analyses were done to identify predictor variables. A 95% confidence interval and adjusted odd ratio were reported. P values less than 0.05 were considered statistically significant in the multivariable analysis. Results. This study showed that iodized salt was adequately utilized by 61.1% (CI = 57%–65%) of households. Good knowledge of iodine deficiency disorder (AOR = 2.25, 95% CI = (1.44, 3.50)), keeping salt in the kitchen house away from fire (AOR = 5.09, 95% CI = (3.25, 7.98)), buying packed salt [AOR = 1.89, 95% CI = (1.12, 3.19)), keeping salt in a covered container (AOR = 2.18, 95% CI = (1.24, 3.81)), and exposing salt to sunlight (AOR = 0.39, 95% CI = (0.23, 0.65)) were significantly associated. Conclusion. In the district, adequately iodized salt utilization was low. Therefore, it is necessary to enforce the current law for merchants to sell iodized packed salt and teach the community how to handle it.